The winner's curse under behavioral institutions - Nadine Chlaß (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Empirically, social dilemma under information asymmetry are often much less pronounced than theory predicts. Traders experience a winner's curse and maintain efficiency enhancing exchange of commodities when theory predicts none. Especially under competition, cursed parties undergo severe losses and thereby fund social welfare. Hence, if one cures the winner's curse, one often decreases social welfare. Here, I test how market efficiency can be maintained without individual losses. In a competitive common value auction, parties sidestep both market inefficiency and a winner's curse by judging quality-by-price, and setting price-by-quality.
Keywords: D61; D82; L13; 330; imperfect information; common value auction; price-quality relation; Auktionstheorie; Unvollkommene Information; Allokationseffizienz; Theorie